Treating acute exacerbations of chronic bronchitis and community-acquired pneumonia: How effective are respiratory fluoroquinolones? - Balter, M. (College of Family Physicians of Canada, 2006)
OBJECTIVE: To provide family physicians with a review of evidence supporting fluoroquinolone therapy for defined patient populations with acute exacerbations of chronic bronchitis (AECB) and community-acquired pneumonia (CAP). QUALITY OF EVIDENCE: A MEDLINE search found surveillance studies, randomized controlled trials, outcome studies, and expert consensus opinion. Descriptions of patient populations for which fluoroquinolone therapy is recommended are based on level I and level III evidence. MAIN MESSAGE: A growing body of evidence supports fluoroquinolones as first-choice agents for treatment of AECB or CAP patients with comorbidity or a recent history of antibiotic use. Judicious and targeted therapy using fluoroquinolones among patients at risk of infections of the lower respiratory tract should contribute to improved clinical outcomes and broader health care savings. CONCLUSION: Current data show clinical utility and cost-effectiveness of fluoroquinolones in lower respiratory tract infections. The most recently issued AECB and CAP guidelines now recommend these antimicrobial agents as first-choice agents for specific patient populations.